The Preemptive Approach of Ulama in Aceh to Eradicating Corruption - Ali, Bukhari; Hanapi, Agustin; Salam, Abdul Jalil; Syauqi, Muhammad; Filzah, Nadhilah (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2024)
Corruption in Aceh has become a serious issue, with its corruption rates over the past decade being above average compared to other provinces in Sumatra and nationally. Efforts to eradicate corruption do not solely rely on law enforcement agencies but also require the participation of various parties, including religious leaders. The study aimed to analyze the perspectives and participation of ulama (scholars) in Aceh in combating corruption. It employed an empirical legal research method with a sociological anthropological approach. The results of this study indicated that corruption in Aceh was a complex issue that requires a holistic approach and cross-sector collaboration. Ulama plays an important role in eradicating corruption through preaching and religious education that instills the values of amar ma’ruf nahi munkar (enjoining what is good and forbidding what is wrong). However, their involvement is limited to the general public without direct access to policymaking. Effective efforts require synergy between ulama, law enforcement, the government, and society to create a corruption-free culture.